PELAKSANAAN HUBUNGAN MASYARAKAT (HUMAS) MODEL SIMETRIS DUA ARAH DI SMPN I PADEMAWU PAMEKASAN - Mualifah, Mualifah; Nurhadi, Ali (re-JIEM (Research Journal of Islamic Education Management), 2020)
The implementation of a two-way symmetrical model of public relations provides opportunities for recipients of education services to obtain their rights as consumers of education services. This study uses a qualitative approach to the type of case study research. The results showed that: first, the application of a two-way symmetrical model of public relations was carried out in the form of various school programs, this was because it involved outside agencies both government and non-government agencies, communication established by public relations officers ie two directions, mutual giving and receiving, honesty and openness and not on the basis of personal interests. Second, supporting factors in the form of approaches taken by public relations officers, regarding the communication carried out, and the same vision and goals are also supporting factors. Third, the inhibiting factors are internal and external factors. The ability of the public relations officer in planning the program of activities, as well as the approach with whom to aim for and the lack of activity time and readiness of the agency. Fourth, the solution is the principal's policy to immediately take other actions.